PENGARUH PEMBANGUNAN PASAR KALIMPORO TERHADAP LANSKAP FISIK DAN ARUS LALU LINTAS DI KAJANG KABUPATEN BULUKUMBA SULAWESI SELATAN - Bau, Qadriathi Dg (Jurnal Environmental Science, 2024)
The construction of markets plays a crucial role in supporting the smooth flow of development by providing services for buying and selling various types of goods and services that support community life. However, the presence of markets can undeniably have various impacts, especially on surrounding traffic. This study aims to analyze the level of road traffic service resulting from the construction of markets, with a focus on Kalimporo Kajang Market in Bulukumba Regency, South Sulawesi. Data collection was conducted through field surveys that included vehicle volume, road capacity, side friction, and road geometry. This data was then analyzed using calculation methods from the Indonesian Highway Capacity Manual (MKJI). The results showed that the level of traffic service resulting from the construction of Pasar Kalimporo Kajang is at level A, indicating free flow, low volume, and high speed. Additionally, drivers can choose their desired speed, thus not disrupting the two-way traffic performance on the Tanete-Bonto Bahari main road.